Las cavernas y el poblamiento prehispánico de la provincia de Chachapoyas 1 - Ruiz Estrada, Arturo (2008)
Chachapoyas is a Peruvian province of the Amazon region in which the pre-hispanic society whose name is also Chachapoyas flourished Some of the material remains which they bequeathed to us have been studied, nevertheless there is no reported research of the subterranean space they used. That is why this paper deals with the study of several caverns identified in the Chachapoyan territory, in order to corroborate the pre-hispanic settlements there were, in addition to the use they had in ancient times. Furthermore, it draws attention to the utilization of current speleological resources, and to the need of further research in these underground cavities.